IPTEKS AUDIT INTERNAL PADA PT. BANK SULUTGO MANADO - Rondonuwu, Feilen Grace; Rundengan, Fanda D.P. (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Internal auditing or internal inspection is a part contained in a company that plays a role in an organization or company that functions to test and see how activities in an organization or company are carried out or carried out.According to Sukrisno Agoes in his book Auditing (examination of accountants) it was stated that: "Internal audit is an examination of the operations of a company, including accounting policies and operational policies that have been determined by management, to determine whether the operations have been carried out effectively, efficiently, and economical." The same applies to PT. Bank Sulutgo, the internal audit is carried out and carried out in accordance with the functions, duties / responsibilities and authorities that have been set by the bank / company, so that internal controls are carried out effectively and efficiently accompanied by high supervision procedures, to avoid deviations made by irresponsible party.Keywords : internal audit, internal inspection